Development of optical pulse compression techniques - Chin, Mee Koy (2008)
To study techniques for controlling the duration of ultrashort (femtosecond) optical pulses by using the properties of group velocity dispersion (GVD) and self-phase modulation (SPM) in optical fibres and diffraction gratings. To develop techniques for generating nanosecond optical pulses from optically pumped solid statee lasers.